PENGARUH MANAJEMEN KONFLIK DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI PADA BIDANG PENATAAN RUANG DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BOGOR - Ilyas, Yasnimar; Devi, Sri (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
An organization really needs conflict management and transformational leadership to improve employee performance.This study aims to determine: The effect of conflict management, the influence of transformational leadership on employee performance in the field of spatial planning in the Office of Public Works and Spatial Planning of Bogor Regency. The results of the study get the regression equation as follows: Y = 2,088 + 0,109X1 + 0,845X2, which means that every increase in the value of independent variables (conflict management and transformational leadership) will increase the value of employee performance in the field of spatial planning and public works spatial planning of Bogor Regency. The test results of the determination coefficient show that the adjusted R square value is 0.415 (41.5%). In other words, the contribution of the variables of Conflict Management and Transformational Leadership together on Employee Performance is 41.5%, while the remaining 58.5% is explained or influenced by other variables not included in this study. Hypothesis test results both partially and simultaneously prove that conflict management and transformational leadership affect employee performance. The most dominant factor affecting employee performance is transformational leadership, this is evidenced by the regression coefficient of 0.845.